Organogenesis and Development of Corydoras panda in Early Stage - Sulistyowati, D. Tri; Sarah, .; Alifuddin, H. (Indonesian Society of Scientific Aquaculture (ISSA), 2005)
One of attractive ornamental fish species that is from Amazon, South America, is genus Corydoras. This fish has simple body ornament but unique that has black line in its eye and black spot at caudal. The color of C. panda eggs at just after fertilization tends to dark brown and to be transparence after embryo formed. Corydoras larvae possess big yolk egg without oil globule. Larva presents at the bottom of aquarium and position of yolk is beneath of larvae. Egg hatched about 51 hours after fertilization and organogenesis process taken 46 hours. Pro-larvae stage finish after 5-day-old that is marked by no yolk remained. Keywords: organogenesis, embryo, larva, Corydoras panda ABSTRAK Salah satu ikan hias yang berasal dari perairan Amazon, Amerika Selatan adalah Corydoras. Ikan ini memiliki corak tubuh yang sederhana namun unik terdapat garis hitam pada mata dan spot hitam pada pangkal ekor yaitu spesies Corydoras panda. Warna telur ikan Corydoras panda pada awal fertilisasi cenderung coklat gelap dan menjadi semakin terang setelah terbentuknya embrio. Larva Corydoras memiliki ukuran kuning telur besar tetapi tidak memiliki butir minyak. Larva berada di dasar akuarium dengan posisi kuning telur berada di bawahnya. Telur ikan Corydoras panda akan menetas 51 jam pasca pembuahan dengan proses organogenesis selama 46 jam. Masa pre-larva berakhir setelah larva berumur 5 hari yang ditandai dengan habisnya kuning telur. Kata kunci: Organogenesis, embrio, larva, Corydoras panda